The Influence of Profitability, Leverage, Green Accounting and Type of Industry on Corporate Social Responsibility Disclosure - Khairunnisa Khairunnisa; Dewi Kusmayanti (International Journal of Economics Development Research (IJEDR), 2023)
This research examines how profitability, leverage, green accounting, and industry type affect corporate CSR disclosure of non-financial companies on the LQ45 Index that have been registered on the Indonesia Stock Exchange for 2017-2021. This study used quantitative method to collect the data. The sample consists of 12 non-financial companies on the Indonesia Stock Exchange (IDX) list in 2017 to 2021 and are part of the LQ45 stock index. Profitability, leverage, green accounting, and industry type simultaneously influence CSR disclosure. However, partially it does not have inadequate effect on CSR disclosure in non-financial companies on the LQ45 Index that registered on the Indonesia Stock Exchange (IDX) in the year from 2017 to 2021. Increase CSR disclosure through increasing profitability, increasing leverage, choosing companies that report green accounting, and choose a company with the type of industry.